Whistleblower airport security - Clothier, Pip; BBC worldwide (North Sydney, N.S.W. : BBC Worldwide, 2004)
An undercover investigation by the BBC into security at Manchester Airport found shocking security lapses at Britain's third biggest airport. Faulty metal detectors, staff admitting they fiddled bag search figures and staff being tipped off about covert checks were all caught on film by reporter Michelle Cox, who spent ten weeks working undercover as an aviation security officer at the airport
Title from title screen
Executive producer, Lucy Hillman ; camera, Steve Organ ; sound, Billy Young
Reporter: Michelle Cox
DVD format
Keywords: Manchester International Airport -- Security measures; Airports -- Security measures -- Great Britain -- Manchester; Airports -- Great Britain -- Manchester -- Management